2022-RA-646-ESGO Consensus based recommendations for the diagnosis of serous tubal intraepithelial carcinoma, an international delphi study. (20th October 2022) - van Bommel, Majke; Bogaerts, Joep; Hermens, Rosella; Steenbeek, Miranda; de Hullu, Joanne; van der Laak, Jeroen; Simons, Michiel
Abstract : Introduction/Background: Reliable diagnosis of precursor lesions to high grade serous cancer (HGSC) is crucial, for individual patient care, for better understanding its oncogenesis and for research regarding novel strategies to prevent ovarian cancer. These precursor lesions, serous tubal intraepithelial carcinoma (STIC), are difficult to diagnose: the lesion is small, rare, and clear diagnostic criteria are lacking. We aim to optimize STIC diagnosis by providing recommendations for STIC diagnosis, based on international consensus from gynecopathologists. Methodology: A three-round Delphi study was conducted to systematically explore current clinical practice and to reach consensus regarding STIC diagnosis. First, an expert panel consisting of international gynecopathologists was formed. This panel was asked to provide information regarding all relevant aspects of STIC diagnostics, which was used to form a set of statements. Second, the panel rated their agreement on those statements. Third, statements without consensus, according to predefined rules, were rated again by the panel members in the light of the anonymous responses to round 2 of the other panel members. Finally, each expert was asked to either approve or disapprove the set of consensus statements. Results: A panel of 34 gynecopathologists from 11 countries rated their agreement on 64 statements. A total of 27 statements (42%) reached consensus. This set reflects the entire diagnostic workup for pathologists, regarding processing and macroscopy, microscopy, immunohistochemistry, interpretation and reporting. The final set of consensus statements was approved by 76% of the experts. Conclusion: A set of 27 statements regarding STIC diagnosis reached consensus by an international expert panel of gynecopathologists. Those consensus statements contribute to a basis for international standards for STIC diagnosis, which are urgently needed for better understanding of HGSC, for better counselling of patients, and for safely investigating novel preventive strategies for women at high risk of ovarian cancer.